1998
DOI: 10.1523/jneurosci.18-09-03171.1998
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Age-Related Alterations in Synaptic Plasticity by Blockade of L-Type Ca2+Channels

Abstract: The role of L-type Ca 2ϩ channels in the induction of synaptic plasticity in hippocampal slices of aged (22-24 months) and young adult (4-6 months) male Fischer 344 rats was investigated. Prolonged 1 Hz stimulation (900 pulses) of Schaffer collaterals, which normally depresses CA3/CA1 synaptic strength in aged rat slices, failed to induce long-term depression (LTD) during bath application of the L-channel antagonist nifedipine (10 M). When 5 Hz stimulation (900 pulses) was used to modify synaptic strength, nif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
194
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(207 citation statements)
references
References 54 publications
11
194
2
Order By: Relevance
“…[79]) This effect of the oxidative stress is Ca 2+ dependent [87,88,91,92,133,134]; a finding consistent with the fact that calcium inhibits synaptic plasticity. It is noteworthy that treatment with n-3 fatty acids can restore the LTP in aged rats [70,71,[77][78][79].…”
Section: Oxidative Stress and Ltpsupporting
confidence: 68%
“…[79]) This effect of the oxidative stress is Ca 2+ dependent [87,88,91,92,133,134]; a finding consistent with the fact that calcium inhibits synaptic plasticity. It is noteworthy that treatment with n-3 fatty acids can restore the LTP in aged rats [70,71,[77][78][79].…”
Section: Oxidative Stress and Ltpsupporting
confidence: 68%
“…The effects of ageing on hippocampal synaptic plasticity have been studied previously. Significant LTP induction has been shown in rats up to 20±24 months of age, but LTP induction and maintenance in younger animals was easier and proved to be more stable [13,26]. It has been suggested that potentiation deficits in aged rats can only be detected with brief trains of HFS (less than 50 pulses) [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models for ageing, as well as in models for diabetes, hippocampal synapses show plasticity modifications favouring LTD induction [11,34,44], whereas LTP expression and maintenance is impaired [11,45]. In ageing rats, it was shown that an increase in Ca 2+ influx through L-type voltagedependent Ca 2+ channels can lower the LTD induction threshold [26]. Moreover, this Ca 2+ influx would also impair LTP induction by the activation of the Ca 2+ -dependent, K-mediated after-hyperpolarisation [26].…”
Section: Discussionmentioning
confidence: 99%
“…In cultured embryonic hippocampal neurons that are maintained for 28 days, there is an increase in calcium channel activity and in after-hyperpolarization that is accompanied by decreased neuronal survival; blocking L-type calcium channels increased neuronal survival (116). It is interesting to note that the increased after-hyperpolarization is associated with an enhanced induction of long-term depression in CA1 pyramidal neurons and an impaired induction of long-term potentiation (105). Thus, insofar as LTP and LTD may be related to synaptic plasticity during learning (87), these age-related changes suggest a possible basis for cognitive impairment in aging rats (105).…”
Section: Neuron Death Is Not Inevitable Nor the Only Cause Of Age-relmentioning
confidence: 99%
“…It is interesting to note that the increased after-hyperpolarization is associated with an enhanced induction of long-term depression in CA1 pyramidal neurons and an impaired induction of long-term potentiation (105). Thus, insofar as LTP and LTD may be related to synaptic plasticity during learning (87), these age-related changes suggest a possible basis for cognitive impairment in aging rats (105).…”
Section: Neuron Death Is Not Inevitable Nor the Only Cause Of Age-relmentioning
confidence: 99%